Influence of Political Skill and Servant Leadership Toward Career Satisfaction in PT. Bank Tabungan Negara (Persero) Tbk – Surabaya Branch Office - Tesdanahadi, Fatory; Kistyanto , Anang (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This research aimed to explain and analyze the influence of political skill and servant leadership on career satisfaction among employees PT. Bank Tabungan Negara (Persero) Tbk – Surabaya Branch Office. This study used quantitative methods to obtain data taken from the result of an online questionnaire for employees, with a response rate of 57%. The populations of this study were employees of PT. Bank Tabungan Negara (Persero) Tbk - Surabaya Branch Office. The sampling technique used was saturated sampling method on 40 organic employees. The data analysis used in this research was Partial Square (PLS) by using smartPLS 3.0 software. The research showed that political skill has no effect on career satisfaction. The further results revealed that servant leadership has a significant positive effect on career satisfaction. The findings of this study provided banking company managers with a way to identify the constructs that best in explaining servant leadership, especially during these times of the Covid-19 pandemic. All employees needed to improve the quality of the agenda that was held outside working hours that aimed to strengthen relations between employees such as seminars, arisan, and gatherings that could train communication to improve political skill. In addition, the company was advised to increase career satisfaction surveys so the level of employee satisfaction with their careers could be known so that employees remain loyal to the company.